1978
DOI: 10.1152/jn.1978.41.6.1592
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive responses of neurons in medial thalamus and their relationship to spinothalamic pathways

Abstract: 1. An extracellular study of the cat medial thalamus has revealed four types of somatosensory neurons. These were located primarily in the n. parafascicularis, n. subparafascicularis, and n. centralis lateralis; none were found in the n. centrum medianum. There was no functional segregation of neurons within each nucleus or between nuclei. Each type of neuron had large and often bilateral receptive areas. No somatotopic organization of neurons was found within the medial thalamus. 2. Noxious (N) and noxious-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(53 citation statements)
references
References 0 publications
4
49
0
Order By: Relevance
“…Interestingly, these responses reflect in many ways the properties of neurons in the MITN that have projections to cingulate cortex and have large and bilateral receptive fields that are mainly nociceptive but with some tap responses, and a large percentage of nociceptive multimodal responses. 29,30 Acute nociceptive responses in human include those that are mediated by cingulate cortex, which is one of the most frequently activated regions in the pain neuromatrix. 4, 5 Lenz et al 31 used subdural recording electrodes to show that laser-evoked, nociceptive potentials could be evoked directly from the MCC with latencies of 211-242 milliseconds for negative and 325-352 milliseconds for positive potentials.…”
Section: Nociceptive Neurons and Large Aggregate Responsesmentioning
confidence: 99%
“…Interestingly, these responses reflect in many ways the properties of neurons in the MITN that have projections to cingulate cortex and have large and bilateral receptive fields that are mainly nociceptive but with some tap responses, and a large percentage of nociceptive multimodal responses. 29,30 Acute nociceptive responses in human include those that are mediated by cingulate cortex, which is one of the most frequently activated regions in the pain neuromatrix. 4, 5 Lenz et al 31 used subdural recording electrodes to show that laser-evoked, nociceptive potentials could be evoked directly from the MCC with latencies of 211-242 milliseconds for negative and 325-352 milliseconds for positive potentials.…”
Section: Nociceptive Neurons and Large Aggregate Responsesmentioning
confidence: 99%
“…It is unlikely that cingulate responses may participate in the precise sensory encoding of stimulus features, given the poor intensity coding properties and very large receptive fields of CC neurons (Casey, 1966;Dong et al, 1978;Sikes and Vogt, 1992;Yamamura et al, 1996) and the reported fact that pain cannot be localized despite preserved CC if the lateral somatosensory areas are destroyed (Ploner et al, 1999). Moreover, electrical microelectrode stimulation at pMCC sites where pain-sensitive neurons were recorded does not elicit pain sensations (Hutchinson et al, 1999).…”
Section: Functional Significancementioning
confidence: 99%
“…Such pathways may be direct, such as the spino-thalamic cortical pathway (Dong et al 1978;Burstein et al 1996;Willis and Westlund 1997) and others may be indirect, such as cortico-cortical pathways or cortical-subcortical pathways. 'Bilateral' representation at the level of the cortex may also be due to bilateral receptive fields terminating in the spinal cord or brainstem.…”
Section: Activation In the Somatosensory Regionmentioning
confidence: 99%